2013
DOI: 10.3892/etm.2013.1189
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and hepatoprotective properties of Acanthus ilicifolius alkaloid A and its derivatives

Abstract: Acanthus ilicifolius alkaloid A (4-hydroxy-2(3H)benzoxazolone, HBOA) is a naturally occurring compound that has been separated from Acanthus ilicifolius. Previous studies have reported the beneficial effects of HBOA on HSC-T6 cells. This study was undertaken in order to synthesize HBOA and two of its derivatives, specifically, 4-acetoxy-2(3H)-benzoxazolone (AcO-BOA) and 3-acetyl-4-acetoxy-2-benzoxazolone (TC-3), and to investigate the hepatoprotective potentials of these three compounds on CCl4-induced liver i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…exhibited significant anti-inflammatory activity against carrageenan-induced edema in rats [3]. 4-hydroxy-2 (3H) -benzoxazolone is a naturally occurring alkaloid of A. ilicifolius have shown to attenuate the increased TNF-α levels in an acute liver injured mice [8]. A similar effect was observed with indomethacin (1840 pg/ml) and BOA treatment on the TNF-α level.…”
Section: Arumugam and Thiruganasambanthammentioning
confidence: 62%
See 1 more Smart Citation
“…exhibited significant anti-inflammatory activity against carrageenan-induced edema in rats [3]. 4-hydroxy-2 (3H) -benzoxazolone is a naturally occurring alkaloid of A. ilicifolius have shown to attenuate the increased TNF-α levels in an acute liver injured mice [8]. A similar effect was observed with indomethacin (1840 pg/ml) and BOA treatment on the TNF-α level.…”
Section: Arumugam and Thiruganasambanthammentioning
confidence: 62%
“…In recent years, plant extracts obtained using supercritical CO 2 extraction technique has been widely accepted since it employs extraction of bioactive molecules at low temperature, allowing the thermolabile substance to be extracted without destruction, and results in the production of high-quality extracts that are free toxic chemical solvents. Earlier reports indicated that BOA and its structurally related analogs [7][8][9] were present in this species and the synthetic derivatives of BOA were claimed for their anti-inflammatory and antinociceptive effects [10][11][12]. BOA is also toxic allelochemical produced in plants to protect them against herbivores [13].…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological activity and chemical synthesis of active ingredients of HBOA have recently been reported in the literatures concerning about its anti‐inflammatory, analgesic, and antioxidant actions . The protective effect of HBOA against acute liver fibrosis in mice was also evaluated by our study group .…”
Section: Discussionmentioning
confidence: 92%
“…The whole‐plant extract has been reported to possess analgesic and anti‐inflammatory activities . In the prior study, an attempt was made to evaluate the synthesis and hepatoprotective properties of A. ilicifolius alkaloid A and its derivatives . Methanolic extract of the leaves has been reported to exhibit antioxidant, antimicrobial, hepatoprotective, and tumor inhibition activities .…”
Section: Introductionmentioning
confidence: 99%
“…MDA is a key index of lipid peroxidation. By detecting the activity of MDA, lipid peroxidation of liver tissues may be detected, indicating the influence of CCl 4 on liver health (21). GSH is a crucial antioxidant and free radical scavenger, which is able to combine with free radicals and heavy metals to transform harmful toxins into harmless substances for excretion (22).…”
Section: Discussionmentioning
confidence: 99%